Thermal stability and microstructure of fluorine-free hydrophobic coatings of gas diffusion layers for fuel cell applications - Tritscher, Florian; Pranter, Alexander; Blaschke, Fabio; Napetschnig, Werner; Fuchs, Maximilian; Machado-Charry, Eduardo; Hacker, Viktor; Bodner, Merit (Frontiers in Energy Research, 2024)
Polytetrafluoroethylene (PTFE) is used as commercial hydrophobic treatment for gas diffusion layers (GDL) in polymer electrolyte fuel cells. This commercial hydrophobic treatment can reduce the electrical conductivity of GDLs and is facing an uncertain future due to the pending restriction of perfluoroalkyl substances (PFAS). Previously, we proposed surfactant doped polyaniline (PANI) coatings as a fluorine-free alternative hydrophobic treatment. Due to their anti-corrosion properties as well as the electrical conductivity, these coatings offer additional benefits for the GDL compared to PTFE. Prior work demonstrated improved maximum power of a low temperature polymer electrolyte fuel cell (LT-PEFC) using the PANI coated GDL compared to the commercial PTFE treated reference. Based on these findings, additional investigations are needed to optimize the coating and assess possible areas of applications. With this study, we propose the use of the coating in high temperature PEFCs due to its thermal stability determined via thermogravimetric analysis of polyaniline doped with different types of surfactants. A main focus of this work is the investigation of the uniformity and overall porosity of the polyaniline coatings on GDLs via µCT supported by deep learning. This analysis is complemented with fluid dynamics simulations to determine the tortuosity and the gas flow through the GDL. In the future, this approach could enable the optimization of the fluorine-free hydrophobic coatings in combination with the different layers of the membrane electrode assembly (MEA) such as the GDL and the catalyst layer to prevent mass transport limitations.